ANALISIS DESKRIPTIF PERILAKU LESBIAN NARAPIDANA DI LAPAS PEREMPUAN KELAS IIA TANGERANG - Putri, Larisa Aurelia; Aulia, Qisthina (Yayasan Education and Social Center, 2024)
This research was motivated by the problem of lesbian behavior for prisoners, especially at the Class IIA Tangerang Penitentiary. Lesbians are a type of sexual deviation which is one component of homosexual behavior, where homosexuality itself is a type of sexual deviation which is a side effect of two individuals of the same sex. Some groups view the lesbian phenomenon as deviant behavior that is contrary to religious norms. Lesbians are often depicted as a marginalized group in society. Normal women may be motivated to become women who like the same sex by having very intense encounters. This is because female prisoners have limited freedom and little time to spend with men, so they choose to have relationships with other female prisoners in prison. The driving factor for female prisoners to become lesbians is because there is a form of transmission from prisoners who are indicated to be lesbians to prisoners who have normal sexual personalities